Effect of nutrient management on growth, productivity and nutrient uptake of rainfed clusterbean (Cyamopsis tetragonoloba)in arid region - RATHORE, V S; SINGH, J P; SONI, M L; BENIWAL, R K (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during rainy (kharif season of 2004 and 2005 to study the effect of chemical and biofertilizer on growth, yield and nutrient uptake of rainfed clusterbean (Cyamopsis tetragonoloba (L.) Taub). Significant improvement in growth, yield and nutrient uptake was recorded with sole and integrated application of nutrients through chemical fertilizers and bio fertilizers. Application of chemical fertilizers registered significant improvement in seed yield over control and magnitude of increase with application of 50,75 and 100 % of recommended dose of fertilizer (20 kg N, 40 kg P,O, ha) was 21.1,45.6 and 50.9 % over the control respectively. Association between Rhizobium and phosphate solublising bacteria was synergistic and inoculation of both fertilizers significantly improved the seed yield. Bnoculation of Rhizobiunr, phosphate solublising bacteria and Rhizobium + phosphate solublising bacteria recorded 21 .O, 14.0 and 24.6 % higher seed yield than the control respectively. Integration of biofertilizer with chemical fertilizer @ 50 % recommended dose of fertilizer brought significant improvement in yield and nutrient uptake over the respective sole application of chemical and biofertilizer and was comparable with application of 100 %recommended dose of fertilizer.